2020
DOI: 10.1097/hjh.0000000000002296
|View full text |Cite
|
Sign up to set email alerts
|

Real-world efficacy and safety of nebivolol in Korean patients with hypertension from the BENEFIT KOREA study

Abstract: Objective: The efficacy and safety of nebivolol in patients with hypertension is well established, but its effect in Asian patients with essential hypertension in the real world has not been studied. Methods: Adult South Korean patients with essential hypertension, with or without comorbidities, were enrolled to participate in this prospective, single-arm, open, observational study; 3011 patients received nebivolol either as monotherapy or add-on therap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…The prevalence of hypertension is known to differ by age and sex. Nebivolol has been reported to be efficacious and well tolerated for achieving BP control in patients with hypertension in randomized studies as well Values are presented as number (%) AE adverse event, ADR adverse drug reaction real-world observational studies [16,17]. However, studies investigating age and sex differences in the efficacy and safety of nebivolol in patients with hypertension are scarceour age and sex-based subanalysis from the large, observational BENEFIT-KOREA study provides further evidence to support clinicians managing patients with hypertension.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The prevalence of hypertension is known to differ by age and sex. Nebivolol has been reported to be efficacious and well tolerated for achieving BP control in patients with hypertension in randomized studies as well Values are presented as number (%) AE adverse event, ADR adverse drug reaction real-world observational studies [16,17]. However, studies investigating age and sex differences in the efficacy and safety of nebivolol in patients with hypertension are scarceour age and sex-based subanalysis from the large, observational BENEFIT-KOREA study provides further evidence to support clinicians managing patients with hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…Details of the study design and methodology are available in the primary manuscript of the BENEFIT-Korea study [17]. The study was conducted in accordance with the ethical principles that have their origins in the Declaration of Helsinki.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the recent Korean study conducted among 3250 participants reported that nebivolol can be utilized to improve BP outcomes in hypertensive patients with and without comorbidities, either alone or in conjunction with other antihypertensive medications. Most side effects were mild such as dizziness (1.3%), headache (1.0%), and dyspnea (0.9%) 60 .…”
Section: Nebivololmentioning
confidence: 99%